PENGARUH PENAMBAHAN INDOLE ACETIC ACID (IAA) PADA PELAPIS KITOSAN TERHADAP MUTU DAN MASA SIMPAN BUAH JAMBU BIJI (Psidium guajava L.) ‘CRYSTAL’ - Soesiladi E. Widodo; Zulferiyenni Zulferiyenni; Icha Maretha (JURNAL AGROTROPIKA, 2012)
The research was aimmed at (1) studying the effects of the addition of IAA into chitosan coating on the fruit qualities and shelf-life of guava ‘Crystal’, and obtaining the best concentration of IAA added into the chitosan coating to maintain the fruit qualities and prolong the shelf-life of guava ‘Crystal’. The treatments were arranged in a factorial 3 x 3 in a completely randomized design with three replications. The first factors were fruits without any treatment but water (K0), acetic acid 0.5% (K1), and 2.5% chitosan (K2). The second factors were the concentrations of IAA in three levels: 0 (A0), 5 (A1), and 10 μM (A2). The results showed that (1) the chitosan coatings of 2.5% concentra-tion was effective in prolonging the fruit self-life of guava ‘Crystal’ 2.56 and 6.45 days longer compared to the control and acetic acid 0.5%, (2) IAA application did not prolong the fruit shelf-life, and did not decrease the fruit qualities, and (3) the addition of 0.5% acetic acid as a solvent in 2.5% chitosan did not cause a bad affect, but soaking in 0.5% acetic acid as a main solution adversely affected the fruit qualities and shelf-life of guava ‘Crystal’ Key words: guava, IAA, chitosan, browning, quality